Of Temples and Trees: The Black Dragon King and the Arbortourists - Chau, Adam Yuet (The international journal of religious tourism and pilgrimage, 2018)
The intersection of tourism and religion as two more or less coherent systems of political-economic and symbolic-conceptual productions is premised on a crucial conceptual and physical domain, i.e. the sites themselves that are being visited by the tourists and pilgrims. What unites tourists, pilgrims and local worshippers is the act of visiting sites, which suggests that we might wish to call them by a unified term: site visitors. And their practice can be called site visiting. Using materials collected in the mid-1990s in rural north-central China (Shaanbei, northern Shaanxi Province), supplemented with more recent documentary materials, I shall show how a local popular religious temple dedicated to a certain Black Dragon King (Heilongdawang) succeeded in tapping into the expanding environmentalist discourse in China and grafting a treeplanting enterprise (a hilly-land arboretum) onto the existing temple complex, thus attracting visitors to the temple site from far and wide. This is a story of the transformation of a site that changes the overall configuration of the sitescape by incorporating elements that are new, which in turn attract new categories of site visitors (i.e. tree-planters or arbortourists). Many different kinds of social actors were involved in bringing together the disparate domains that are religion, forestry, environmentalism and schools. The case study I present is a tree-planting visit to the Black Dragon King Temple in 1998 of a group of environmentalist-activists and students from Beijing (18 hours away by chartered bus). It illustrates how the temple and the temple boss tried to capture the powerful outside' to bolster the temple's legitimacy, how metropolitan and global environmentalism articulated with folk environmentalism, and how a certain kind of tourism (what I call arbortourism) interfaced with a religious site despite the fact that the site-visitors ostensibly ignored the religious attributes of the site, all the while with the full corroboration of their local hosts who also elected to only highlight the environmentalist agenda of tree planting and downplay the magical efficacy of the Black Dragon King. As a result of these efforts of mutual dissimulation a sort of theatre was staged, with a happy outcome for both parties.